2023
DOI: 10.2174/1874609816666230525161020
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic Obesity and Its Impact on Quality of Life: A Concise Review

Abstract: The presence of sarcopenia and obesity is a feature of sarcopenic obesity (SO). In this condition, the fat-to-lean body mass ratio is incorrect. Excess visceral fat, the percentage of body fat, subcutaneous fat, and body mass index causes poor health and premature death and has been linked to conditions such as type 2 diabetes, ischemic heart disease, high blood pressure, and several types of cancer. In addition, control, autonomy, self-actualization, and enjoyment are all components of quality of life; factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Since the concomitant presence of obesity, sarcopenia, and osteoporosis represents a dreadful trio potentially occurring in postmenopausal women and individuals of advanced age, as each of these conditions is related with adverse outcomes in terms of morbidity, quality of life, and mortality [16], recent works have tried to identify clinical potential early biomarkers and factors further involved in OSO development [17]. Interestingly, a few studies have suggested that high serum ferritin levels are strongly linked to metabolic syndrome, obesity, impaired muscle quality, and sarcopenia [18].…”
Section: Biomarkersmentioning
confidence: 99%
“…Since the concomitant presence of obesity, sarcopenia, and osteoporosis represents a dreadful trio potentially occurring in postmenopausal women and individuals of advanced age, as each of these conditions is related with adverse outcomes in terms of morbidity, quality of life, and mortality [16], recent works have tried to identify clinical potential early biomarkers and factors further involved in OSO development [17]. Interestingly, a few studies have suggested that high serum ferritin levels are strongly linked to metabolic syndrome, obesity, impaired muscle quality, and sarcopenia [18].…”
Section: Biomarkersmentioning
confidence: 99%
“…Donini et al (pp. 252-255) in this year's section nicely illustrated that the concomitant presence of sarcopenia, obesity, and osteoporosis ('osteosarcopenic obesity') represents a dreadful trio particularly occurring in postmenopausal women as each of these conditions is related to adverse outcomes in terms of morbidity, quality of life, and mortality [14]. Also, in chronic diseases such as chronic obstructive pulmonary disease (COPD), a greater prevalence of muscle wasting, weakness, and exercise limitations have been observed in females than in males [15,16].…”
mentioning
confidence: 99%